2020
DOI: 10.1371/journal.pone.0239275
|View full text |Cite
|
Sign up to set email alerts
|

The R2R3-MYB gene family in banana (Musa acuminata): Genome-wide identification, classification and expression patterns

Abstract: The R2R3-MYB genes comprise one of the largest transcription factor gene families in plants, playing regulatory roles in plant-specific developmental processes, defense responses and metabolite accumulation. To date MYB family genes have not yet been comprehensively identified in the major staple fruit crop banana. In this study, we present a comprehensive, genome-wide analysis of the MYB genes from Musa acuminata DH-Pahang (A genome). A total of 285 R2R3-MYB genes as well as genes encoding three other classes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 45 publications
(66 reference statements)
3
47
0
Order By: Relevance
“…In general, R2R3-MYB domains have, on average, approximately 108 amino acids between each MYB protein ( Liu et al, 2020 ; Pucker et al, 2020 ). Outside the DNA-binding domain, however, the length and the composition of amino acids vary greatly.…”
Section: Resultsmentioning
confidence: 99%
“…In general, R2R3-MYB domains have, on average, approximately 108 amino acids between each MYB protein ( Liu et al, 2020 ; Pucker et al, 2020 ). Outside the DNA-binding domain, however, the length and the composition of amino acids vary greatly.…”
Section: Resultsmentioning
confidence: 99%
“…Our expression study that was based on published RNA-Seq data (Pucker et al, 2020a), revealed highest MusaF3H1 transcript abundance in early developmental stages of pulp and intermediate stages of peel development, while highest MusaF3H2 expression was found in adult leaves (Table 1). This is, at first glance, in contrast to the quantitative real-time PCR (qRT-PCR)-derived expression data presented by Pandey et al (2016), reporting high transcript levels of MusaF3H1 and MusaF3H2 in young leaves and bract.…”
Section: Musaf3h1 and Musaf3h2mentioning
confidence: 84%
“…The final pathway analyses were mostly based on the tool Mercator4 and Mapman4 [35]. In addition, differential expressed MYB genes were functional annotated based on several datasets Arabidopsis thaliana MYBs [36], Beta vulgaris MYBs [37], Musa acuminata MYBs [38], Croton tiglium MYBs [39], Dioscorea rotundata MYBs and Dioscorea dumetorum MYBs via KIPEs (https://github.com/bpucker/KIPEs). GO term assignment and enrichment were performed using Blast2GO [40] via OmicsBox with cutoff 55, Go weight 5, e-value 1.e-6, HSP-hit coverage cutoff 80 and hit filter 500.…”
Section: Methodsmentioning
confidence: 99%
“…The final pathway analyses were mostly based on the tool Mercator4 and Mapman4 [35]. In addition, differential expressed MYB genes were functional annotated based on several datasets Arabidopsis thaliana MYBs [36], Beta vulgaris MYBs [37], Musa acuminata MYBs [38], Croton tiglium MYBs [39], Dioscorea rotundata MYBs and Dioscorea dumetorum…”
Section: Data Processing and Functional Analysismentioning
confidence: 99%